The gadis restaurant : food and beverages / Nur Haslinda Azmi ... [et al.] - Azmi, Nur Haslinda; Harun, Umi Hanani; Ishak, Ifah Fahanis; Habib Alnsar, Nur Athirah; Abdullah@Mohd Hilman, Nurul Natasha (2021)
This business plan was prepared for Madam Hafini Suhana Bt Ithnin as we will provide to her about our business that we already planned to achieve it. The name of our company is THE GADIS RESTAURANT and our restaurant has its uniqueness in where all the workers in our company are female. This also can give job opportunities to all ladies out there as we hired employees who can give a full commitment to the company, have high patience in handling situation, serve the customers with full of care and many more. The nature of this business is in food and beverages and will be operating on 1st January 2020. The Gadis Restaurant was located at The Gadis Restaurant, No.35, Jalan 5/25a, Wangsa Maju, 53300 Kuala Lumpur. The Chief Owner of The Gadis Restaurant is Nur Athirah Binti Habib Alnsar that responsible for developing the business plan to start the business, setting a strategic mission and vision to move the restaurant forward with success. The General Manager is Ifah Fahanis Binti Ishak that responsible for managing the staff, hiring and training the employees and supervise the daily operations of the restaurant. The Assistant Manager is Nurul Natasha Binti Abdullah @ Mohd. Hilman that responsible for handling the customer’s complaints and resolve all the issues at the restaurant. The Finance Manager is Nur Haslinda Binti Azmi that responsible for budget planning and gives financial advice. The Kitchen Manager is Umi Hanani Binti Harun that responsible for overall operations for the kitchen area of the restaurant. The factor in selecting the proposed business is we want to serve the customers with traditional food from Javaness descent such as Nasi Ambeng at an affordable price. We also want to provide the customers with great services and they will come back again as they satisfied with our services. It is important for planning the right dishes to be put on the menu where we should include the type of menu such as meatless vegans and vegetarian options like pecal, options for families to dine like Nasi Ambeng and a side dish. The purpose of this business plan is to help the entrepreneur to manage the budget to finance the business and to manage the operation of the company to make it a success.